1997
DOI: 10.1080/15216549700205081
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of endogenous antioxidant enzymes in naturally occurring hypertrophic cardiomyopathy

Abstract: We have recently developed a porcine model with naturally occurring hypertrophic cardiomyopathy (HCM). Similar to humans, occluded intramural coronary artery and damaged mitochondria are frequently observed in these animals in which the disease is thought to be associated with the local ischemia of myocardium. In view of antioxidant functions involved in the ischemic injury, we measured the expression of endogenous antioxidant enzymes in the tissues with and without HCM. The results showed a significant increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
1
8
1
Order By: Relevance
“…Accordingly, in symptomatic HCM patients, lower catalase activity is observed, while the levels of other antioxidant enzymes, including mitochondrial superoxide dismutase (SOD) and glutathione peroxidase (GPX), are unaltered [87]. Similar findings were reported in a pig model of naturally occurring HCM [88]. Notably, elevated oxidative stress is an established driver of left ventricular hypertrophy and fibrosis in HCM models [84][85][86][89][90][91], which suggests that this event precedes the progression of the disease from the asymptomatic to the symptomatic form.…”
Section: Hypertrophic Cardiomyopathysupporting
confidence: 58%
“…Accordingly, in symptomatic HCM patients, lower catalase activity is observed, while the levels of other antioxidant enzymes, including mitochondrial superoxide dismutase (SOD) and glutathione peroxidase (GPX), are unaltered [87]. Similar findings were reported in a pig model of naturally occurring HCM [88]. Notably, elevated oxidative stress is an established driver of left ventricular hypertrophy and fibrosis in HCM models [84][85][86][89][90][91], which suggests that this event precedes the progression of the disease from the asymptomatic to the symptomatic form.…”
Section: Hypertrophic Cardiomyopathysupporting
confidence: 58%
“…19 Other redoxregulating proteins, such as thioredoxin (TXN), GPX1, and Cu-Zn superoxide dismutase (SOD1) also have been implicated in regulating cardiac hypertrophy and failure. 18,20,21 We detected no significant changes in the expression levels of GPX1 and HOMX1 in the ␤-MyHC-Q403 rabbits. We could not determine expression levels of TXN and SOD in the heart because of lack of reliable assays in rabbits.…”
Section: Circulation Research August 5 2005mentioning
confidence: 77%
“…Decreased expression level of CAT mRNA has been observed in a porcine model with naturally occurring HCM. 18 Catalase, which reacts very efficiently with H 2 O 2 to form water and molecular oxygen, in conjunction with GPX1 are the primary responsible enzymes for the removal of H 2 O 2 . Although it is plausible that reduced expression level of CAT could provide for a mechanism for the excess levels of H 2 O 2 in the hypertrophic conditions, we did not detect significant reduc- …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in general, oxidative stress is determined by an imbalance between ROS and antioxidant-defense capacity, and it has been reported that the activity of catalase, an antioxidant, is decreased in hearts from a porcine model of spontaneously occurring HCM (28), which suggests that lower antioxidant capacity may also contribute to the enhanced oxidative stress in HCM hearts.…”
Section: Other Possible Sources Of Enhanced Oxidative Stress In the Hmentioning
confidence: 99%